Investigation of the attitudes, needs, and expectations of the Saligny community. (2nd January 2018) - Constantin, A.; Constantin, M.; Diaconu, D.
Abstract: Many countries encourage national forums for transparency, dialogue and participation with regards to radioactive waste disposal. However, the local actors (authorities, non-government organisations and the public) often note a lack of public participation in the decision making process. Civil society is often frustrated with its limited involvement in the consultative process. Participation is regulated by national laws and rules and the right to participate in environmental decision-making is covered by the Aarhus Convention. Continuous dialogue amongst stakeholders is seen as important in building sustainable solutions in radioactive waste management. In addition, understanding public concerns and needs can increase the trust between the partners and build confidence in the process. Different national and local contexts have contributed to the development of quite a broad set of approaches and tools for stakeholder engagement. This paper describes the use of such tools in the engagement with the Saligny community in the siting process of a repository for low- and intermediate-level wastes in Romania. Some specific issues are highlighted such as: the low level of interest amongst the public in relation to long-term projects; over-estimation of benefits in comparison to the negative aspects of hosting a repository; lack of a coherent public voice; and a perceived lack of information on the project from the authorities and the implementer. The present study describes the setting up of the participatory approach to engage with the public and the different methods employed (including citizen juries, workshops, open days, etc.). A number of criteria were developed for evaluating the effectiveness of these methods particularly with regards to their adaptability to a local context such as Saligny. The paper then focuses on the results of one of these methods – the use of focus groups covering a cross-section of civil society – including members of the general public, a group of professionals and a group of local councillors. The study has resulted in a number of recommendations to the implementer on how to build a new programme for public participation.